2019
DOI: 10.1007/s10826-019-01585-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Coping, and Quality of Life in Families with a Child with ASD Living Regionally

Abstract: Objectives: The present study aimed to explore whether regionality is associated with differing stress levels, coping, QOL and daily routines for parents and families of a child with ASD (aged 2-18 years) in Western Australia using validated outcome measures and compare the stress levels and QOL of this group to population norms. Methods: A sample of 278 families living in Western Australia who have a child or adolescent (2-18 years old) with a clinical diagnosis of ASD participated in a cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Current literature has shown that caregivers of neurodivergent children experience a lower quality of life than caregivers of typically developing children (MacKenzie & Eack, 2022 ; Vaz et al, 2021 ). This lower quality of life is largely attributed to meeting the demands associated with providing ongoing care and support (Parsons et al, 2020 ). Current services for caregivers include caregiver training programs, education, support groups and respite (Lovell & Wetherell, 2019 ; Vaz et al, 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Current literature has shown that caregivers of neurodivergent children experience a lower quality of life than caregivers of typically developing children (MacKenzie & Eack, 2022 ; Vaz et al, 2021 ). This lower quality of life is largely attributed to meeting the demands associated with providing ongoing care and support (Parsons et al, 2020 ). Current services for caregivers include caregiver training programs, education, support groups and respite (Lovell & Wetherell, 2019 ; Vaz et al, 2021 ).…”
mentioning
confidence: 99%
“…While there are many known services to support caregivers, knowledge of their specific effectiveness, relevance and accessibility are limited (Iadarola et al, 2018 ). The most frequently reported challenges as expressed by caregivers include a lack of social support, financial stress, fear for the future, and lack of parent education and training about accessing government funding and services (Daniels et al, 2017 ; Parsons et al, 2020 ; Vaz et al, 2021 ).…”
mentioning
confidence: 99%
“…[ 33 34 35 ] Other studies have also shown an association between sleep problems and quality of life. [ 36 37 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…An overall search of the documents showed a wide range of sources related to autistic individuals and their families' quality of life, which has been published by a number of researchers, including Parsons et al [42], Coales et al [43], Vasilopoulou and Nisbet [44], and Alotaibi [45]. Nevertheless, studies investigating autism in media are remarkably limited.…”
Section: Selection Of Sourcesmentioning
confidence: 99%